Cutaneous melanoma in patients treated with tumour necrosis factor inhibitors: a retrospective series of 15 patients. (13th December 2013) - Chabbert, C.; Adamski, H.; Guillet, G.; Sassolas, B.; Misery, L.; Perrinaud, A.; Machet, L.; Quereux, G.; Esteve, E.; Solau‐Gervais, E.; Saraux, A.; Polard, E.; et al.
Abstract Background Several case reports suggested that tumour necrosis factor‐α (TNF) inhibitors might increase the incidence and/or alter the natural course of melanoma towards a more aggressive behaviour. Objective Our objective was to point if history of melanoma in patients exposed to TNF inhibitors could present with a particular pattern at diagnosis or during follow‐up. Methods We performed a retrospective multicentre study settled in the West part of France to collect and analyse all cases of patients with melanoma who received anti‐TNF therapy. Results Fifteen cases were included. First, 10 patients (mean age: 55.6 years; sex ratio: 1) had a melanoma diagnosed after TNF inhibitors initiation. The mean duration between initiation of treatment and melanoma was 48.7 months. Two patients died of metastatic disease. Second, four patients had a past history of melanoma before anti‐TNF therapy (mean duration of treatment: 10.8 months). None experienced a progression of melanoma disease. Last, one woman had a past history of melanoma before and then developed a second melanoma when exposed to biotherapy. Conclusion Our case series does not reveal a distinct profile of melanoma in the patients exposed to TNF inhibitors. Additional prospective trials including larger number of patient are needed to demonstrate the possible link between biological therapy with TNF inhibitors and development of melanoma.